Non-Compliance Of Forestry Permits With Regional Spatial Plan (RTRW) In Siak Regency - Suardi; Ellydar Chaidir; Suparto (Jurnal Ilmu Pendidikan dan Sosial, 2026)
The inconsistency between forestry permits and the Regional Spatial Plan (RTRW) has become a significant issue in natural resource governance in Siak Regency. This study aims to analyze the forms of non-compliance of forestry and plantation permits with the 2020–2040 Siak Regency RTRW, identify indications of maladministration in the licensing process, and formulate policy measures to strengthen spatial planning compliance. This research employs a normative legal approach supported by qualitative analysis and quantitative-spatial data. The data were obtained through the examination of statutory regulations, spatial planning documents, forestry and plantation permit data, field observations, and interviews with key informants. The findings reveal that Industrial Plantation Forest (HTI) permits covering 126,737 hectares and plantation permits covering 57,866 hectares operate outside the spatial allocation corridors stipulated in the Siak Regency RTRW. This mismatch indicates problems of intergovernmental coordination, weak spatial verification, and the suboptimal implementation of monitoring and sanction mechanisms. The impacts are not merely administrative but also include legal uncertainty, agrarian conflicts, peat ecosystem degradation, and increased vulnerability to forest and land fires. This study recommends the formulation of a regent regulation as a technical guideline for RTRW implementation, the strengthening of the Regional Spatial Planning Coordination Team (TKPRD), the integration of licensing data through GIS and the One Map Policy, periodic audits of problematic permits, and the enforcement of administrative sanctions in the form of permit cancellation or revocation against corporations proven to have violated spatial planning regulations.